News & Views: Complex order in soft matter - Glotzer, Sharon C.; Engel, Michael (Nature, 2011)
Spherical micelles can aggregate into highly organized structures. New micelle arrangements mimic known atomic crystals, both periodic and aperiodic, and provide evidence for a material with 18-fold rotational symmetry.